Design & simulation of hydrogen based hybrid green power system using sea water for Cox's Bazar. Issue 1 (1st January 2017) - Kabir, Kazi Meharajul; Matin Bhuiyan, Mahmud Abdul
Abstract: Hydrogen energy is one of the favorite choice to alternative power generation around the world. Renewable energy is the best scope to produce alternative power. Because resources are available and doesn't make any green house effect. In this reason to establish a renewable resources (solar, wind) based hybrid system with sea water electrolysis by Proton exchange membrane (PEM) electrolyzer for the production of Hydrogen. In this proposed system PV & Wind power use for sea water electrolysis and storage Hydrogen. To meet the peak load demand Gas Turbine Generator used to produce electricity using storage Hydrogen fuel. For design, optimization & peak load demand we have chosen Diabatic beach, Kolatoli Cox's Bazar where wind flow, solar radiation and sea water are available.